Management of Cultural Resources in the Riouwstraat Area (LLRE Martadinata) in Bandung from the Perspective of Cultural Resources Management - Santika, Denny (Budapest International Research and Critics University, 2021)
Riouwstraat area in Bandung from the perspective of cultural resources management (CRM) is an effort to manage cultural heritage areas in the midst of the widespread use of cultural heritage buildings for business purposes. The background of the transfer of cultural heritage functions occurs because of the transformation process that is supported by various factors, namely: economic which is also related to socio-cultural conditions, strategic location, and government policies. The Riouwstraat area management strategy is carried out by identifying and analyzing important values. The solution for managing this area is sought to accommodate the interests of investors while still upholding conservation; synergize the interests of stakeholders with policy makers; and prioritizing the principle of benefit to society.